Relative age effects and team performance among elite beach handball athletes - Savassi Figueiredo, L.; De Castro Ribeiro, L.; Alves Pereira Fialho, J. V.; Da Silva, D. G.; Gantois, P.; De Conti Teixeira Costa, G.; De Souza Fonseca, F. (Journal of Physical Education and Sport, 2020)
The Relative Age Effect is a well established phenomenon in a wide range of elite team sports. However,the prevalence of this effect was not investigated in beach handball so far. Therefore,this study aimed to investigate whether RAEs are present in elite beach handball athletes and to analyze its relation with team competitive success in World Championships. Data from 777 elite beach handball athletes (391 males and 386 females) from 32 countries who participated in the IHF Beach Handball World Championships (2012 to 2018) were analyzed. Athlete`s birth dates were organized according to quarters, based on their month of birth, as follows; Q1 (from January to March), Q2 (from April to June), Q3 (from July to September), and Q4 (from October to December). Athletes` birthdates were compared according to sex and the rankings achieved in Beach Handball World Championships. We performed Chi-squared tests to examine whether sex and final placements modulated RAEs in beach handball sports system. An over representation of athletes born in the first semester was found for both sexes (p < 0.05). An over representation of athletes born in Q1 was found, compared to athletes born in Q3 (p < 0.007) and Q4 (p < 0.001) in male athletes.In females, athletes born in Q1 and in Q2 were more prevalent than athletes born in Q4 (p < 0.05). The athletes` birthdates distribution was different from expected (p < 0.001) for intermediate classification teams, but not for top-4 (p = 0.139) and bottom-4 (p = 0.103) ranked teams. In conclusion, RAEs were found in both male and female elite beach handball athletes in senior category. However, RAEs were not associated with competitive success, determined by the final ranking achieved by the national teams in the World Championships.